The new global agenda and the future of the multilateral development bank system - Amarendra Bhattacharya; Homi Jamshed Kharas; Mark Plant; Annalisa Prizzon (Kiel Institute for the World Economy (IfW), 2018)
The authors assess the role of the multilateral development system and the reforms needed to support the new global agenda. There is an urgency to the reforms. The coming decades will see the largest urban expansion in history. More infrastructure needs to be built in the next 15 years than the existing stock of infrastructure in the world. Multilateral development banks (MDBs) are uniquely placed to support policy and institutional reforms and build institutional capacity, enhance the quality of projects and programs, and scale up for transformative change. They are the best mechanism today for leveraging public resources. By our calculations, each dollar of paid-in capital could reasonably translate into 50 of public investments if properly allocated. Despite these inherent strengths, MDBs are constrained by their financial and institutional capacities, effectiveness of instruments, and unclear mandates and governance shortcomings. The authors suggest MDBs do more in three client groups: (i) fragile states; (ii) high-debt countries; and (iii) upper middle-income countries, adjusting strategies and use of instruments in each case. With so many issues on the table, they believe that the greatest risk to the system lies in active inertia, a tendency to make changes on the margin that fall short of a collective response that is scaled to the task at hand. Individual MDBs each perform well, according to evaluation results, but their impact could be enhanced if they cooperated more as a system and developed scalable platform approaches. Major expansion is not feasible under current business and financial models. Shareholders need to reach consensus on capital and governance to unlock the financial potential and effectiveness of the MDB system.
Keywords: F02; F30; F35; F55; F63; J11; O19; 330; Sustainable Development Goals (SDGs); multilateral development banks; international finance; fragility; Agenda 2030; managing globalization; inclusive growth; poverty reduction; catalytic finance; public private partnerships (PPPs); G20; sustainable infrastructure; global public goods; capital investments; debt management